Productivity and profitability of maize-pumpkin mix cropping in Chitwan, Nepal - Dhakal, Shiva Chandra; Regmi, Punya Prasad; Thapa, Resham Bahadur; Sah, Shrawan Kumar; Khatri-Chhetri, Dilli Bahadur (Journal of Maize Research and Development, 2015)
The study was conducted to determine the productivity, profitability and resource use efficiency of maize-pumpkin mix crop production in Chitwan. The study used 53 maize-pumpkin mix crop adopting farmers from among 300 farmers adopting different pollinator friendly practices. Descriptive and statistical tools including Cobb-Douglas production function were used to analyze data, collected from structured interview schedule. The benefit cost ratio (1.58) indicates that maize-pumpkin mix cropping was profitable with productivity of 2.83 ton per ha on maize main product equivalent basis. The magnitude of regression coefficients of maize-pumpkin mix cropping implied that expenditure on seed and fertilizer and irrigation had significant positive effect on gross return with estimated decreasing return to scale (0.85). According to estimated allocative efficiency indices, it is suggested to increase expenditure on seed and fertilizer cum irrigation by about 90% and 55% respectively. Extension of modern technologies with adjustment on resource use is to be encouraged for increase in productivity and profitability of maize-pumpkin mix crop production which indirectly promotes and ensure forage for pollinators Journal of Maize Research and Development (2015) 1(1):112-122 DOI: http://dx.doi.org/10.5281/zenodo.34290